Modernization of Marriage Guidance (Bimwin) from a Maslahah Perspective at the Kua, Tinambung District, Polewali Mandar Regency - Mudriyanah; Muh. Irsyad Fattah; Kurniati; Asni (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the modernization of Marriage Guidance (Bimbingan Perkawinan/Bimwin) from the perspective of maṣlaḥah at the Office of Religious Affairs (KUA) of Tinambung District, Polewali Mandar Regency. The research focuses on three objectives: (1) to analyze the implementation of Bimwin modernization, (2) to identify the supporting and inhibiting factors, and (3) to examine the modernization process from the perspective of maṣlaḥah. The study was motivated by the increasing divorce rate and rapid social changes that require marriage guidance services to become more adaptive, innovative, and responsive to the needs of prospective couples. This field research employed normative Islamic theological and sociological approaches. Primary data were collected through observation, interviews, and documentation involving the Head of KUA, religious counselors, SIMKAH operators, and Bimwin participants, while secondary data were obtained from books, scientific journals, regulations, and official documents. The findings reveal that Bimwin modernization has been implemented through SIMKAH Web and E-Bimwin services, digital learning media, participatory teaching methods, contextual learning materials, and flexible guidance approaches. Supporting factors include government policies, adequate facilities, competent counselors, and increased public awareness, whereas budget limitations, technological infrastructure, digital literacy, and participant adaptation remain the main challenges. From the maṣlaḥah perspective, the modernization of Bimwin reflects maṣlaḥah mursalah by enhancing service quality, strengthening marriage preparedness, and promoting resilient and harmonious families while preserving Islamic values and local Mandar wisdom.